Model Predictive Control of a pH neutralization Process - Nanyan, Muhammad Nadhir (Universiti Teknologi PETRONAS, 2018)
The purpose of this project is to research the Model Predictive Control (MPC) system on controlling a pH neutralization process. Nowadays, pH neutralization process is widely used in industry especially in chemical process. pH neutralization process in industry is needed to make sure that process will be more efficient, more quality product and environment protection. The study will be focusing on analysing and comparing MPC with Proportional-Integral-Derivative (PID) control strategy. To make the simulation of pH plant and designing the controller, transfer function and behaviour of pH plant is needed. Hence to get a transfer function or model of pH plant, mathematical modelling was created by using Matlab/Simulink. Besides that, Statistical Modelling identification technique also has been used to identified transfer function of a pH plant. Both controller (MPC and PID) will be simulate by using Matlab/Simulink based on process model. The comparison between two control methods will be observed using several performance measures including overshoot, settling time, steady state error and time delay.